About Structural Identifiability of Nonlinear Dynamic Systems under Uncertainty (Global Journal of Science Frontier Research, 2018)
Approach to the analysis of nonlinear dynamic systems structural identifiability (SI) under uncertainty is proposed. This approach has a difference from methods applied to SI estimation of dynamic systems in the parametrical space. Structural identifiability is interpreted as of the structural identification possibility a system nonlinear part. We show that the input should synchronize the system for the SI problem solution. The structural identifiability estimation method is based on the analysis of the framework special class. The input parameter effect on the possibility of the SI estimation of the system is studied.
Keywords: framework; nonlinear dynamic system; phase portrait; structural identification; nonlinearity; structural identifiability; synchronizability